Risk Reporting Practices in UK PLC's - Shah, Aditya (2009)
This dissertation basically studies the current risk reporting practices in some of the UK PLC are listed in FTSE 250 index. This study compares the risk disclosures made by 10 firms in 2005/06 with 2008/09 to find certain patterns and changes during this time. A Content analysis was done on 20 annual reports to find the total amount of risk disclosures and the various categories of risks mentioned in the reports. An absolute increased in the total volume of the risk disclosures was found on comparisons. Also, it was found that firms are increasing the amount of forward looking information compared to historic information on risk. The other findings suggest that firm’s disclosure of financial risks has decreased with additional focus going to areas such as environmental and market risk disclosures. However, the annual reports fail to give out quantitative values to such data making them highly subjective and lack richness. Moreover, there was inconsistency in the reporting practices of firms found. Further studies need to be done in this area so as to evolve a better culture of risk reporting and to make it more beneficial to end users.